Fascist voices : an intimate history of Mussolini's Italy - Duggan, Christopher (Oxford University Press, 2013)
Today Mussolini is remembered as a hated dictator who, along with Hitler and Stalin, ushered in an era of totalitarian repression unsurpassed in human history. But how was he viewed by ordinary Italians during his lifetime? In Fascist Voices, Christopher Duggan draws on thousands of letters sent to Mussolini, as well as private diaries and other primary documents, to show how Italian citizens lived and experienced the fascist regime under Mussolini from 1922-1943. Throughout the 1930s, Mussolini received about 1,500 letters a day from Italian men and women of all social classes writing words o.